Characterization of full-length long noncoding RNAs and identification of virus-responsive lncRNAs in Sogatella furcifera - Ban, Yawen; Cui, Ting; Zhao, Lifei; Li, Xue; Bai, Qing; Wu, Qingfa (Frontiers in Microbiology, 2025)
Long non-coding RNAs (lncRNAs) are crucial regulators of development and stress responses in eukaryotes, but their roles in non-model insects, particularly rice planthoppers, remain poorly characterized. Here, we present a comprehensive identification and characterization of full-length lncRNAs in the white-backed planthopper (Sogatella furcifera), a major rice pest and efficient vector of Southern rice black-streaked dwarf virus (SRBSDV). By integrating PacBio single-molecule real-time (SMRT) sequencing with publicly available Iso-Seq datasets, we reconstructed a high-confidence, full-length transcriptome and identified 1,211 lncRNAs spanning 1,174 loci. These lncRNAs displayed canonical features, including lower GC content, shorter transcript length, and fewer exons. Unlike mRNAs, which exhibited extensive alternative splicing, only 21 splicing events were detected among lncRNAs. Stage-specific lncRNAs were predominantly expressed during embryogenesis (e.g., 93 transcripts between 0 and 72 h post-oviposition) and molting (e.g., 16 in pre-ecdysis), while sex-biased expression patterns emerged after 24 h. Functional enrichment analysis linked male-biased lncRNAs to metabolic pathways and molting-associated lncRNAs to tissue remodeling processes, including Wnt signaling. Upon SRBSDV infection, approximately 50% of differentially expressed lncRNAs responded to both virus exposure (feeding on infected plants) and confirmed viral replication, exhibiting distinct sex-dimorphic regulation. K-means clustering defined four major expression modules: female-biased (Cluster 1), male-biased (Cluster 2), and two virus-suppressed clusters (Clusters 3 and 4), which were significantly enriched for immune-related pathways such as PI3K-Akt signaling and phagosome formation. We further experimentally validated five sex-independent virus-responsive lncRNAs, sfur_LNC0242, sfur_LNC1059, sfur_LNC0956, and sfur_LNC0346 (upregulated), and sfur_LNC0483 (downregulated), with predicted involvement in NF-κB signaling, ubiquitin-mediated proteolysis, and metabolic adaptation through AMPK/PPAR pathways. Altogether, this study provides the first full-length lncRNA reference for S. furcifera and reveals the dynamic regulation of lncRNAs across development and in response to viral infection. The identification of sex-specific and conserved virus-responsive lncRNAs offers promising molecular targets for disrupting vector competence and advancing RNAi-based pest management strategies.